History of Education and Covid-19: The crisis of the school according to african (Akanbi, Chisholm), american (Boto, Civera, Cunha, Kinne, Rocha, Romano, Rousmaniere, Southwell, Souza, Taborda, Veiga, Vidal) and european (Depaepe, Escolano, Magalhães, Nóvoa) researchers - Honorato, Tony; Nery, Ana Clara Bortoleto [UNESP] (Universidade Estadual de Maringa, 2020)
What possible types of knowledge or devices develop from research in the History of Education for in-depth understanding and the assessment of impacts of the Covid-19 pandemic in School Education? This question was answered by renowned researchers in the field of History of Education: Agustín Escolano Benito (Spain); Alicia Civera (Mexico); Andrea Bennett-Kinne (USA); António Nóvoa (Portugal); Antonio Romano (Uruguay); Carlota Boto (Brazil); Cynthia Greive Veiga (Brazil); Diana Gonçalves Vidal (Brazil); Gizele de Souza (Brazil); Grace Oluremilekun Akanbi (Nigeria); Heloísa Helena Pimenta Rocha (Brazil); Justino Magalhães (Portugal); Kate Rousmaniere (USA); Linda Chisholm (South Africa); Marc Depaepe (Belgium); Marcus Aurélio Taborda de Oliveira (Brazil); Maria Teresa Santos Cunha (Brazil); Myriam Southwell (Argentina). Answers are given in full and they have been distributed within five non-compartmentalized themes in text organization: 1) Suspension, decline of the school model; 2) Territoriality and the right to education: South Africa, Argentina, Brazil, US and Nigeria; 3) Places-spaces, times and materials of school cultures; 4) Health and divergent sensitiveness in education; 5) De-schooling, old innovations and present time between impositions and resistances.
História da Educação e Covid-19: crise da escola segundo pesquisadores africanos (Akanbi, Chisholm), americanos (Boto, Civera, Cunha, Kinne, Rocha, Romano, Rousmaniere, Southwell, Souza, Taborda, Veiga, Vidal) e europeus (Depaepe, Escolano, Magalhães, Nóvoa)
Keywords: coronavírus; covid-19; historiography; history of education; sars-cov-2; school